Jamur yang diisolasi dari Daun dan Batang Bergejala Sakit pada Tanaman Karet (HeveabrasiliensisMuell.Arg.) di Kabupaten Sanggau - Riza Linda, Veronika, Mukarlina, (Jurnal Protobiont, 2015)
The rubber tree(Hevea brasiliensis Muell.Arg.) at a certain age can be attacked by diseases caused by fungi. The symptoms of the disease may be form blackish brown spots on the stems, blackish white patches on the petiole, the tip of the leaf wrinkled, etc. This research aimed to find out the types of fungi isolated from the leaves and stems with symptoms of disease on the rubber tree at different age levels. The samples were taken using a cruise method based on the age level i.e. 0-9 months old, 2-5 years old, and > 5 years old. The research findings indicated that there were seven types of fungi found i.e. Fusarium V1, Colletotrichum V2, Phytophthora V3, Aspergillus V4, Penicillium V5, Mucor V6 and Chrysonilia V7. The leaves aged 0-9 months old the fungi found were Colletotrichum V2, Phytophthora V3, and Penicillium V5; on the leaves aged 2-5 years old i.e. Phytophthora V3 and Aspergillus V4; and at age > 5 years old, Fusarium V1, Phytophthora V3, Mucor V6 and Chrysonilia V7 were found on the stem organ.